Seasonal variation and spatial distribution of microplastics in tertiary wastewater treatment plant in South Korea - Kim, Min-Ji; SANG HEON NA; Rida Batool; Insu Byun; Kim, Eun Ju (Elsevier BV, 2022)
Wastewater treatment plant (WWTP) is proposed to be a point source of microplastics (MPs) that enter aquatic environments. Here, we quantified and characterized MPs down to 20 mu m at a tertiary WWTP in Korea over a 1year period. All wastewater contained MPs during the monitoring period, with concentrations ranging from 114 +/- 17-216 +/- 65 particles/L for influent and from 0.26 +/- 0.29-0.48 +/- 0.11 particles/L for effluent. MP abundance in the influents showed significant seasonal differences whereas a seasonal trend was not observed for the effluents, indicating a stable treatment performance (approx. 99.8%) of the WWTP. Spatial surveys of MP distribution in the WWTP showed that most MPs were removed by coagulation-sedimentation and rapid sand filtration, but some MPs still remained in the final effluent to generate the potential annual load of 2.9 x 109 particles and 0.54 kg into the rivers. These findings highlight the importance of long-term monitoring and MP mass quantification that would promote more accurate estimation of the MP load from WWTPs.